Integrating Fuzzy Logic and Dynamic Programming in Multithreaded Concurrent File Transfer Schemes - Sermeno, Jason P.; Orquia, John Jowil D. (2021 Second International Conference on Innovative Technology Convergence (CITC), 2021)
The advancement in the architecture of multicore processors leads to the rapid development of multithreaded concurrent file transfer utilities. The ability to split a process into subprocesses and perform multiple series of Input/Output (I/O) read-write file operations simultaneously aids the program to speed up the data transmission process. However, copying or moving files using multithreading techniques has a shortcoming when with dealing I/O file operations that are performed within multiple threads especially when there is a bulk of background processes taking place in the system or the system hardware profile is low. In this paper, we propose an alternative scheme for multithreaded concurrent file transfer methods by integrating it with fuzzy logic and dynamic programming (DP) algorithm. Using the proposed model will maintain a good balance on the number of threads being spawned and distributes a consistent number and weight of the files to be processed for each thread, thus, making it more smart and effective in handling shared resources and improving the data transmission rate.